Surface modification of rGO with PEG for the improvement of water/salt selectivity of CTA/rGO nanocomposites for desalination membrane applications. (21st September 2022) - You, Meng; Yao, Dongxue; Xu, Fei; Zhang, Chenchen; Meng, Jianqiang
Abstract: Reduced graphene oxide (rGO) was functionalized with polyethylene glycol (PEG) and utilized as fillers to improve the cellulose triacetate (CTA)/rGO nanocomposite performance for desalination membrane applications. Thiolated PEG was tethered to rGO by thiol-ene chemistry and then blended with CTA to prepare nanocomposite films via solution casting followed by solvent evaporation. The effects of rGO-PEG content and PEG molecular weight (MW) on the water and salt transport properties were investigated based on the solution-diffusion theory. Both the water sorption and sorption selectivity increase after adding of rGO-PEG. The water permeability is diffusion dependent and increases due to the water transport channel through the interlayer spacing of rGO. The CTA/rGO-PEG nanocomposites exhibit a lower salt diffusivity and permeability due to film densification and screening out salt ions by rGO interlayer spacing. Although modification of rGO with PEG can enhance compatibility, the best combination of water permeability and water/salt selectivity was achieved for nanocomposites from low rGO-PEG loading and low PEG MW. Graphical abstract: Image 1 Highlights: rGO-PEG content and PEG molecular weight affect water and salt transport. rGO-PEG increases both water sorption and sorption selectivity of nanocomposites. Interfacial compatibility of nanocomposites is improved by grafting PEG on the rGO. Nanocomposite with low rGO-PEG loading and low PEG MW shows the best selectivity.